Ketahanan Keluarga pada Pasangan yang Belum Memiliki Keturunan - Hanan Abimanyu; Abid Rohmanu; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2025)
This study aims to explore and understand the concept of family resilience in couples who do not yet have children in Balerejo Village, Kebonsari District, Madiun Regency. Family resilience is essential to study because even though they have not been blessed with children, these couples can still maintain the integrity and harmony of their household. This study is a qualitative study with a phenomenological approach. Data were collected through in-depth interviews with four couples who experienced the absence of children in their married life. Data analysis techniques were carried out thematically to find patterns of meaning that shape family resilience. The study results show that family resilience is formed through several essential aspects: open communication, emotional support between couples, involvement in religious activities, and utilization of social resources in the surrounding environment. In addition, couples also demonstrate the ability to manage psychological stress, develop survival strategies, and maintain hope for having children. The strength of interpersonal relationships, spirituality, and adaptation to reality influences the success of couples in preserving family integrity even without children. These findings provide important insights into family survival strategies and resilience, which can be used to strengthen social and psychological interventions for couples in similar situations.